2015
DOI: 10.4103/1596-3519.149880
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbances among patients with epilepsy in Nigeria

Abstract: There is a high frequency of sleep disorders among PWE. Clinicians should screen PWE for sleep disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 24 publications
(41 reference statements)
2
1
1
Order By: Relevance
“…Our main objective was to identify sleep disorders in patients with epilepsy. Our study showed that depression is more common in patients with epilepsy than in healthy controls, as also indicated previously 15,16 . The higher frequency of depression in patients with epilepsy can be explained as an effect of having a chronic disease 17 .…”
Section: Discussionsupporting
confidence: 91%
“…Our main objective was to identify sleep disorders in patients with epilepsy. Our study showed that depression is more common in patients with epilepsy than in healthy controls, as also indicated previously 15,16 . The higher frequency of depression in patients with epilepsy can be explained as an effect of having a chronic disease 17 .…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to earlier observations made by Klobucnikova et al [12] who compared epilepsy patients showing clinical epileptic seizures at night with patients suffering from epilepsy but did not show epileptic seizures while sleeping, in this study, we could not find that epilepsy patients had In this study, we found that epilepsy may have a negative impact on sleep. This was consistent with previous studies, which suggested that epilepsy can worsen sleep architecture and severity of sleep disorders [13][14][15][16]. Possibly the repetitive seizures impacted the sleep by reducing total sleep time and decreasing REM [13].…”
Section: Discussionsupporting
confidence: 92%
“…The finding from this study was lower than a study conducted in Nigeria [39]. The variation may be due to measurement tool difference (Epworth sleepiness score tool was used in a study conducted in Nigeria whereas the PSQI tool was used in this study).…”
Section: Discussioncontrasting
confidence: 72%